2005
DOI: 10.1007/s00221-005-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurophysiological effects of delayed training following a small ischemic infarct in primary motor cortex of squirrel monkeys

Abstract: A focal injury within the cerebral cortex results in functional reorganization within the spared cortex through time-dependent metabolic and physiological reactions. Physiological changes are also associated with specific post-injury behavioral experiences. Knowing how these factors interact can be beneficial in planning rehabilitative intervention after a stroke. The purpose of this study was to assess the functional impact of delaying the rehabilitative behavioral experience upon movement representations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 32 publications
2
56
1
1
Order By: Relevance
“…35,36 Delayed stroke rehabilitation may reduce the efficacy of treatment, ultimately limiting functional recovery in patients. 37,38 Upregulation of growth-promoting factors and increased excitability in the peri-infarct cortex and contralateral cortex may be involved in shaping this critical period. 21,22,39 In our study, CIMT was initiated at poststroke day 7 and persisted for 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Delayed stroke rehabilitation may reduce the efficacy of treatment, ultimately limiting functional recovery in patients. 37,38 Upregulation of growth-promoting factors and increased excitability in the peri-infarct cortex and contralateral cortex may be involved in shaping this critical period. 21,22,39 In our study, CIMT was initiated at poststroke day 7 and persisted for 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TMS could be used to achieve a strengthening or modification of a network that is specific for a diminished cognitive function. Studies have suggested that the best way to perpetrate this strengthening is to stimulate the area and activate the network supporting the specific function (Barbay et al, 2006). This approach can be achieved by combining exogenously induced plasticity (i.e., brain stimulation) with a specific training-induced plasticity (i.e., cognitive training).…”
Section: Miniussi and Rossinimentioning
confidence: 99%
“…This indicates that the reorganization of the brain is different from that induced by the training started earlier. Moreover, these multi-joint responses in the forearms 9) showed a negative correlation with the behavioral improvement in clinical evaluation 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Barbay et al indicated that delayed training resulted in an increase of co-contractive movements evoked with microstimulation 9) . This suggests motor skill training in the chronic stages following stroke may modulate peri-infarct cortical plasticity in a different way.…”
Section: Introductionmentioning
confidence: 99%